Giant Cell Tumor on Tendon Sheath of the Hand: The Incidence of Recurrence, Functional Outcomes and a Literature Review - G, Kastanis; M, Bachlitzanaki; P, Kapsetakis; C, Christoforidis; C, Chaniotakis; A, Pantouvaki (International Journal of Innovative Research in Medical Science, 2020)
Giant Cell Tumor on Tendon Sheath (GCTTS) of the hand is a benign nodular tumor originated from tendon sheath of the tendons and the joints and is the second most common soft tissue tumor of the hand after ganglion cyst. The aim of this study is to evaluate 79 cases of giant cell tumor of tendon sheath of the hand and to analyze the postoperative functional outcomes and recurrence rate of the tumor in a mean period of five years follow up. Material and Methods: Fifty five subjects were females and twenty four males with an average age of 38,8 years-old (range23-65 years old) were included in this study. The most frequent location of tumor was the index finger (32/79 patients, 40,5%). The majority of patients was presented in outpatient’s clinic for a painless swelling on volar side of the digit, while only 13(16,45%) patients presented for painful mass and numbness of the digit in 7(8,9%) cases. All cases were categorized by Al-Qattan classification system with type I lesion in 51(64,5 %) cases and type II in 28(35,5 %) cases. Dimension of tumors macroscopically varied from 0,4cm to 5 cm. In 12 cases we reconstructed the A2 pulley to avoid bowstring deformity and eventual postoperative loss of hand function. In 12 cases we reconstructed the A2 pulley to avoid bowstring deformity and eventual postoperative loss of hand function. 8 patents with bone erosion underwent postoperatively complementary local radiotherapy. A standard protocol of rehabilitation was performed in all patients. Results: Results were evaluated according to complications, range of motion, Quick Dash Score and functional satisfaction of patients in a mean follow-up of 49 months. Two major complications presented in this study: 5 cases with transitional neuroapraxia and 6 cases with recurrence of the tumor with a mean of postsurgical period 14,8 months. Finally at last assessment the mean Quick Dash Score was 4,5 (range from 0-11,4) the range of motion was fully recovered in 73 patients while patient’s satisfaction rated from “very satisfied” in 58(73,4%) cases, “satisfied” in 17(21,5) and “dissatisfied” in 4(5,1%) patients. Conclusions: Giant cell tumor of tendon sheath of the hand is a common tumor which presents a high incidence of recurrence in different populations of patients. The goal of treatment is to reduce the recurrence rate and restore a functional hand. The operation procedure should be well planned preoperatively, the tumor must excised en block, dissection must be under surgical loop and must be emphasized to remove satellite lesion while when patients present increased risk factors or inadequate excision of the mass, postoperative radiotherapy is performed.